Effect of results-based financing on facility-based maternal mortality at birth: an interrupted time-series analysis with independent controls in Malawi - De Allegri, Manuela; Chase, Rachel P.; Lohmann, Julia; Schoeps, Anja; Muula, Adamson S.; Brenner, Stephan (BMJ global health, 2019)
Introduction The aim of this study was to assess the impact of a results-based financing (RBF) programme on the reduction of facility-based maternal mortality at birth. Malawi is a low-income country with high maternal mortality. The Results-Based Financing For Maternal and Newborn Health (RBF4MNH) Initiative was introduced at obstetric care facilities in four districts to improve quality and utilisation of maternal and newborn health services. The RBF4MNH Initiative was launched in April 2013 as a combined supply-side and demand-side RBF. Programme expansion occurred in October 2014. - Methods Controlled interrupted time series was used to estimate the effect of the RBF4MNH on reducing facility-based maternal mortality at birth. The study sample consisted of all obstetric care facilities in 4 intervention and 19 control districts, which constituted all non-urban mainland districts in Malawi. Data for obstetric care facilities were extracted from the Malawi Health Management Information System. Facility-based maternal mortality at birth was calculated as the number of maternal deaths per all deliveries at a facility in a given time period. - Results The RBF4MNH effectively reduced facility-based maternal mortality by 4.8 (−10.3 to 0.7, p<0.1) maternal deaths/100 000 facility-based deliveries/month after reaching full operational capacity in October 2014. Immediate effects (changes in level rather than slope) attributable to the RBF4MNH were not statistically significant. - Conclusion This is the first study evaluating the effect of a combined supply-side and demand-side RBF on maternal mortality outcomes and demonstrates the positive role financial incentives can play in improving health outcomes. This study further shows that timeframes spanning several years might be necessary to fully evaluate the impact of health-financing programmes on health outcomes. Further research is needed to assess the extent to which the observed reduction in facility-based mortality at birth contributes to all-cause maternal mortality in the country.